SENYAWA ANTIBAKTERI DAUN BELAWAN PUTIH (TRISTANIOPSIS WHITEANA) - Handayani, Dewi; S. Achmadi, Suminar; Agusta, Andria (JURNAL BIOLOGI INDONESIA, 2014)
Isolation of antibacterial compounds from chloroform extract of belawan putih (Tristaniopsis whiteana) leaves hasbeen done. The bioautography analysis of the extract against Escherichia coli and Staphylococcus epidermidis,subsequently followed by isolation and purification of active compounds led us to obtain two pure compounds,compound 1 and 2. Futhermore, the compound 2 was identified as betulinic acid based on their spectroscopic dataincluding ultraviolet spectrum, infrared spectrum, 1D- and 2D-NMR spectra. In addition, this is the first report ofthe occurrence of this compound in the plant of Tristaniopsis whiteana and the genus of Tristaniopsis.Keywords: antibacterial, active compound, leaves, Tristaniopsis whiteana